THE EFFECT OF ENTREPRENEURSHIP KNOWLEDGE AND SELF-EFFICIENCY ON STUDENTS ENTREPRENEURSHIP INTEREST - Bahri, Bobby Oka Fathur; Marsofiyati; Rachmadania, Rizki Firdausi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of entrepreneurial knowledge and self-efficacy on interest in entrepreneurship. This study uses the census method with a quantitative approach with a population of 11th grade students of SMKN 10 Jakarta in the academic year 2021-2022. The sample in this study were 11th grade OTKP students totaling 74 respondents. Data collection was carried out using a questionnaire instrument with a Likert scale. Entrepreneurial Interest (Y), Entrepreneurship Knowledge (X1), and Self-Efficacy (X2) are primary data. Data were analyzed with multiple regression technique using SPSS (Statistical Product and Service Solution) 25.0 program. The analytical technique used consists of requirements analysis test (normality and linearity test), classical assumption test (multicollinearity test and heteroscedasticity test), multiple regression equations, F test and T test. Normality test with Kolmogorov Smirnov on both variables is 0.200. The results of the linearity test on the entrepreneurial knowledge variable are worth 0.001, and the self-efficacy variable is worth 0.000. The multicollinearity test of the entrepreneurial knowledge variable has a tolerance value of 0.963 and a VIF value of 1.039, the self-efficacy variable has a tolerance value of 0.963 and a VIF value of 1.039. Heteroscedasticity test on the entrepreneurial knowledge variable sig is 0.993, and the self-efficacy variable sig is 0.573. The f-test is worth 13.808 and the t-test of the entrepreneurial knowledge variable is worth 3.029, and the self-efficacy variable is worth 3.629. The result of the multiple regression equation is Y=17.756 + 0.333X1 + 0.255X2. From this equation, the influence of entrepreneurial knowledge and self-efficacy on interest in entrepreneurship has a positive and significant influence. The result of the coefficient of determination (R2) is 0.280. which means that 28% of the variables of interest in entrepreneurship can be explained by entrepreneurial knowledge and self-efficacy, while the remaining 72% is influenced by other variables not examined.